Combined Circulation of Puumala, Tula, Seewis Hantaviruses in the Territory of the Republic of Bashkortostan - P. A. Mochalkin; V. G. Akimkin; S. V. Ugleva; E. S. Morozkin; E. A. Blinova; K. A. Sycheva; D. D. Skripnichenko; T. A. Bondarenko; Yu. O. Epik; M. T. Makenov; A. A. Kazak; A. K. Popova; et al. (Russian Research Anti-Plague Institute “Microbe”, 2024)
The aim of the work was to study the species diversity of pathogenic and non-pathogenic hantaviruses circulating in populations of small mammals in the Republic of Bashkortostan using molecular-genetic methods.Materials and methods. Individual samples from small mammals were tested by the nested PCR using genus-specific primers that amplify the L segment of hantaviruses. The resulting PCR products were sequenced by the Sanger’s method from internal nested PCR primers. For samples containing Puumala virus, fragments of the S, M, and L segments of the viral genome were sequenced using Sanger’s method. The construction of phylogenetic trees was carried out using the MEGA X software.Results and discussion. Out of 300 examined samples of small mammals collected on the territory of the Republic of Bashkortostan in 2023, 14 samples have been found positive for the presence of hantavirus RNA: Seewis (8), Tula (3), Puumala (3). The circulation of the non-pathogenic hantavirus Seewis and the opportunistic hantavirus Tula has been established for the first time in the Republic of Bashkortostan. The circulation of the Seewis hantavirus has been confirmed in populations of the common shrew (Sorex araneus) and the pygmy shrew (S. minutus); the Tula hantavirus – in populations of the common vole (Microtus arvalis). Results of phylogenetic analysis substantiate the reassortment origin of one of the genetic variants of the Puumala hantavirus on the territory of the Republic of Bashkortostan. The prerequisites for the formation of combined natural foci of hantaviruses Puumala, Seewis, and Tula on the territory of the Republic of Bashkortostan are discussed. Цель работы – изучение видового разнообразия патогенных и непатогенных хантавирусов, циркулирующих в популяциях мелких млекопитающих на территории Республики Башкортостан, с помощью молекулярно-генетических методов.Материалы и методы. Индивидуальные пробы мелких млекопитающих протестированы с помощью вложенной ПЦР с использованием родоспецифичных праймеров, амплифицирующих ...